2019
DOI: 10.3390/genes10060417
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis of Hypomyces perniciosus, the Causal Agent of Wet Bubble Disease of Button Mushroom (Agaricus bisporus)

Abstract: The mycoparasitic fungus Hypomyces perniciosus causes wet bubble disease of mushrooms, particularly Agaricus bisporus. The genome of a highly virulent strain of H. perniciosus HP10 was sequenced and compared to three other fungi from the order Hypocreales that cause disease on A. bisporus. H. perniciosus genome is ~44 Mb, encodes 10,077 genes and enriched with transposable elements up to 25.3%. Phylogenetic analysis revealed that H. perniciosus is closely related to Cladobotryum protrusum and diverged from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 92 publications
2
43
1
Order By: Relevance
“…However, sequenced genomes in this genus (Hypomyces/Cladobotryum) are scarce. To date, only the genomes of C. protrusum and H. perniciosa (the sexual morph of M. perniciosa) have been released [17,18]. C. protrusum is the only species of Cladobotryum for which a genome is available [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sequenced genomes in this genus (Hypomyces/Cladobotryum) are scarce. To date, only the genomes of C. protrusum and H. perniciosa (the sexual morph of M. perniciosa) have been released [17,18]. C. protrusum is the only species of Cladobotryum for which a genome is available [17].…”
Section: Introductionmentioning
confidence: 99%
“…Associated advances have improved the identification of pathogenicity-related genes and revealed the molecular mechanisms underlying pathogenesis. To date, several pathogenic genomes have been sequenced using Pacific Biosciences (PacBio) Sequel or the RSII platform [17,18,20]. With these available genomic sequences, it is possible to determine the evolutionary relationships among fungi [21][22][23][24], as well as to explore the evolution of nutritional mode.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fletcher et al [4] reported that non-pigmented white isolates of M. perniciosa are less pathogenic than the pigmented isolates. The moderate to high virulence levels of the yellow to brown M. perniciosa isolates may be due to a large amount of conidia production, and production of secondary metabolites (e.g., pigments and mycotoxins) plays an important role in pathogenesis [12,19]. In contrast, Fletcher et al [4] reported that the less aggressiveness of some of the isolates maybe as a result of mycovirus infecting those strains.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation, gene flow, sexual reproduction (recombination) and the adaptation to diverse fungal hosts might have contributed to the genetic diversity of M. perniciosa from the AFLP analysis. In our previous work [12], the analysis of the genome sequence of M. perniciosa (Hp 10) revealed it is heterothallic species containing MAT 1-2 locus. There is a need for further studies to identify the sexual stages of the isolates to find out whether the sexual stage contributes to the diversity of this pathogen [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation